The Influence of Performance Company, Good Corporate Governance to Corporate Social Responsibility with Good Corporate Governance as moderating variable (Empirical Studies On Non Financial Company Registered In Indonesia Stock Exchange) - Rahmat Efendi; Haryetti '; Sjahruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aim to test influence of Performance Company, Good Corporate Governance to Corporate Social Responsibility with Good Corporate Governance as moderating variable. Research data applies time series obtained from IDX Statistic, and ICMD (Indonesian Capital Market Directory) inscribed in BEI from time line 2009 to 2012. Population in this research is all company non financialand number of samples 52 companies by passing phase purposive sampling. Analysis technique used in this research is doubled linear regression to obtain picture that is totally about relation between variable one with other. And research applies application program Statistical Package for Social Sciences (SPSS) Statistics 21. Result is indicating that all variables influential positive to corporate social responsibility. And result of adjusted R square 91,1% which can influence corporate social responsibility at company non financial BEI.Keywords: Performance Company, Good Corporate Governance, and Corporate Social Responsibility